2012
DOI: 10.1063/1.4739759
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the effective distribution coefficient (K) for silicon impurities

Abstract: For the production of photovoltaic cells, the silicon purity can be intermediate between metallurgical grade silicon (MG-Si, 98%–99.9% pure) and electronic grade silicon (>99.9999% pure). This silicon, with intermediate purity and that still meets solar cell requirements, is called upgraded metallurgical grade silicon (UMG-Si). One method of producing UMG-Si is applying a controlled solidification process, like unidirectional solidification (heat exchange method), zone melting (or zone refining), or Czo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In previous works, Pires et al 18-20 and Mei et al 15,21,22 reported a significant reduction of impurities using VD and ZM techniques. Yuge et al 23 described the purification of MG-Si to SG-Si using the NEDO (New Energy and Industrial Technology Development Organisation) melt-purification process, which adopts a multi-step process involving a sequence of VD, DS, and plasma melting.…”
Section: Purification By the Cz Growth Techniquementioning
confidence: 93%
“…In previous works, Pires et al 18-20 and Mei et al 15,21,22 reported a significant reduction of impurities using VD and ZM techniques. Yuge et al 23 described the purification of MG-Si to SG-Si using the NEDO (New Energy and Industrial Technology Development Organisation) melt-purification process, which adopts a multi-step process involving a sequence of VD, DS, and plasma melting.…”
Section: Purification By the Cz Growth Techniquementioning
confidence: 93%
“…The amount of calcium that transfers from solid phase to liquid phase in the time of t can be expressed by: (1) where C l is the content of calcium in the solid-liquid interface, C s is the content of calcium in solid phase. The segregation coefficient of calcium, k 0 , can be express as follows [18] (2)…”
Section: The Segregation Of Calcium In the Solid-liquid Interfacementioning
confidence: 99%
“…Generally, when the k D is less than 1 (k D <1), the compound distributes into the aqueous phase more than the organic phase. 23 When k D = 1, the solute separates equally in the two phases that are involved, and it could be removed completely from the mixture. This applies when the bulk contaminant where the solute is seized is different from the two liquids that are used to form the binary solvent.…”
Section: Introductionmentioning
confidence: 99%
“…The Partition coefficient technique has been applied in finding the ‘effective partition coefficient’ (k D ) for silicon impurities. 23 As reported, the process uses the impurities solubility difference in solid and liquid silicon called effective partition coefficient (k D ). The measured impurities profiles in silicon are compared with the theoretically calculated impurities profiles to determine the effective partition coefficient.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation